2014
DOI: 10.1152/ajpheart.00585.2013
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of VEGF-C attenuates chronic high salt intake-induced left ventricular maladaptive remodeling in spontaneously hypertensive rats

Abstract: Recent studies have shown that the tonicity-responsive enhancer binding protein (TonEBP)/vascular endothelial growth factor-C (VEGF-C) signaling pathway-induced lymphangiogenesis provides a buffering mechanism for high salt (HS) intake-induced elevation of blood pressure (BP). Moreover, blocking of TonEBP/VEGF-C signaling by mononuclear phagocyte depletion can induce salt-sensitive hypertension in rats. We hypothesized that HS intake could have an impact on cardiac lymphangiogenesis, and regulation of VEGF-C b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…For the determination of cardiomyocyte hypertrophy in the non-infarcted region in hearts 45 days postoperation, heart tissue was fixed in 4% paraformaldehyde, embedded in paraffin, and cut into 7-m sections. After incubation with tetramethylrhodamine isothiocyanate-labeled wheat germ agglutinin (1:200), as previously described (62,65), the wheat germ agglutinin-stained sections were then counterstained with DAPI. The images were acquired and analyzed using Image Pro Plus software to calculate myocardial cross-sectional area.…”
Section: H501mentioning
confidence: 99%
See 1 more Smart Citation
“…For the determination of cardiomyocyte hypertrophy in the non-infarcted region in hearts 45 days postoperation, heart tissue was fixed in 4% paraformaldehyde, embedded in paraffin, and cut into 7-m sections. After incubation with tetramethylrhodamine isothiocyanate-labeled wheat germ agglutinin (1:200), as previously described (62,65), the wheat germ agglutinin-stained sections were then counterstained with DAPI. The images were acquired and analyzed using Image Pro Plus software to calculate myocardial cross-sectional area.…”
Section: H501mentioning
confidence: 99%
“…Long-term LV functional analysis. Two-dimensional (2D) echocardiographic measurements were performed on postoperation day 45, as previously described (36,62). The rats were anesthetized, and transthoracic echocardiography of the LV was performed (Vivid7, GE Medical System, Horton, Norway).…”
Section: H501mentioning
confidence: 99%
“…However, preclinical models predict that reduced levels of VEGF-C would promote hypertension. Consistent with this notion, a recent report showed that overexpression of VEGF-C lowered blood pressure in a model of salt-sensitive hypertension, whereas blocking VEGF-C activity exaggerated the severity of hypertension (55). Nonetheless, chronic hypertension in humans is a complex disorder; it is possible that the observed elevation in VEGF-C levels may reflect tissue resistance to VEGF-C or even a compensatory response.…”
Section: Salt Homeostasis Gets Under Your Skinmentioning
confidence: 82%
“…In another study, TonEBP‐mediated cardiac lymphangiogenesis and macrophage infiltration was observed in the left ventricles of SHRs that were fed a high‐salt diet (Yang et al ., ; Yang et al ., ). Retrovirus‐induced overexpression of VEGFC led to enhanced lymphangiogenesis, reduced myocardial fibrosis and macrophage infiltration, decreased BP and preserved myocardial function.…”
Section: Lymphatics and Hypertensionmentioning
confidence: 99%